Afghanistan–Pakistan shared waters: state of the basins - Shah, Muhammad Azeem Ali; Lautze, Jonathan F.; Meelad, A. (CAB International, 2023)
There is currently no water cooperation between Afghanistan and Pakistan. Of the nine rivers that flow across the border, none possess a formal agreement or mechanism to manage shared water resources. Further, there is very little information available about the status of environment, hydrology and water resources management for these river basins that could be used as a starting point for dialogues on transboundary water coordination. This State of the Basins book co-develops an overview of the three most important river basins, in collaboration with international experts and water professionals from Afghanistan and Pakistan. It covers water resources, land resources, ecological health, environment, climate change, and the social and economic conditions for sustainable management of these precious resources. It will inform decision making within the two countries, and begin to establish benefits that can accrue from more active collaboration on these shared waters. This book: Focuses on portions of the Indus shared by Afghanistan and Pakistan. Features extensive engagement and co-development with Afghan and Pakistani professionals. Is the first book on the shared waters in the Indus, developed in the context of regional realities associated with post-August 2021 Taliban takeover. The book is aimed at students and researchers in water rights and resources, and government decision makers, private sector investors, donors, intermediary organizations that work directly with farmers, researchers and students. It is a reference book for graduate students and researchers working on these basins, and on transboundary river basin management in Asia and beyond.